2006
DOI: 10.1086/504285
|View full text |Cite
|
Sign up to set email alerts
|

ChandraLETG Observations of Supernova Remnant 1987A

Abstract: We discuss the results from deep Chandra LETG observations of the supernova remnant 1987A (SNR 1987A). We find that a distribution of shocks, spanning the same range of velocities (from ∼ 300 to 1700 km s −1 ) as deduced in the first part of our analysis (Zhekov et al. 2005, ApJ, 628, L127), can account for the entire X-ray spectrum of this object. The post-shock temperature distribution is bimodal, peaking at kT∼ 0.5 and ∼ 3 keV. Abundances inferred from the X-ray spectrum have values similar to those for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 34 publications
(49 reference statements)
6
62
0
Order By: Relevance
“…The foreground column is fixed at N H = 2.35 × 10 21 cm −2 [10]. Metal abundances are fixed at values measured by Zhekov et al [13], which are generally consistent with the LMC abundances. Ionization timescales for the soft component (kT ∼ 0.3 keV) are high (n e t > 10 12 cm −3 s), indicating the hot gas is in collisional ionization equilibrium due to the shock interaction with dense CSM.…”
Section: X-ray Spectrummentioning
confidence: 72%
See 4 more Smart Citations
“…The foreground column is fixed at N H = 2.35 × 10 21 cm −2 [10]. Metal abundances are fixed at values measured by Zhekov et al [13], which are generally consistent with the LMC abundances. Ionization timescales for the soft component (kT ∼ 0.3 keV) are high (n e t > 10 12 cm −3 s), indicating the hot gas is in collisional ionization equilibrium due to the shock interaction with dense CSM.…”
Section: X-ray Spectrummentioning
confidence: 72%
“…3b, [12]). The high-quality LETG spectrum showed that the continuous distribution of the shock temperature is represented by two dominant components (kT ∼ 0.5 and 2.5 keV) [13]. The LETG spectrum indicated LMC-like metal abundances with a moderate enhancement in N [13].…”
Section: X-ray Spectrummentioning
confidence: 93%
See 3 more Smart Citations